Analysis of Selling and Service Pricing Mechanisms from an Islamic Economic Perspective - Nurhidayah, Ay’ay; Koni, Agus; Sekhruri, Sekhruri (International Journal of Economics, Management and Accounting (IJEMA), 2023)
This research is motivated by the fact that price determination in various businesses does not fully implement Sharia economic principles. The aim of this research is to determine the analysis of the mechanism for determining selling prices and services from an Islamic economic perspective. The research method used is a qualitative research method. The research results show that every human being needs wealth to fulfill all his life needs. Therefore, humans will always try to obtain wealth. One way to get it is by working. Meanwhile, one form of work is trade or business. Islam, through the example of the Prophet SAW and the caliphs who always maintained their actions, shows how important trade and business are. Islam actively encourages Muslims to do business and trade.